Inhibition of TGFβ signaling and its implications in anticancer treatments - Calone, I.; Souchelnytskyi, S. (Experimental Oncology, 2012)
The transforming growth factor-β (TGFβ) is a potent regulator of tumorigenesis. In cancer, two distinctive behaviors of TGFβ have been reported as a tumor suppressor at early stage of the disease, and as a tumor promoter at later stages. The past decades, the dualistic role of TGFβ has garnered a lot of attention. As a result, cancer researchers’ has been tasked to elucidate how TGFβ signaling may lead to metastatic dissemination, how to tackle carcinogenesis and which therapeutic strategies should be adopted. Consequently, TGFβ signaling pathways have been considered as appropriate targets for cancer therapy. The TGFβ therapeutic strategies have emerged at three levels: ligand, ligand-receptor interaction and intracellular signaling level. Promising inhibitors of TGFβ signaling have entered clinical trials and shown encouraging results. Here we review the three strategies of TGFβ signaling inhibition and theirs applications in treatment of cancer.